A new approach to synchrotron energy-dispersive X-ray diffraction computed tomography - Lazzari, Olivier (Journal of synchrotron radiation, 2012)
A new data collection strategy for performing synchrotron energy-dispersive X-ray diffraction computed tomography has been devised. This method is analogous to angle-dispersive X-ray diffraction whose diffraction signal originates from a line formed by intersection of the incident X-ray beam and the sample. Energy resolution is preserved by using a collimator which defines a small sampling voxel. This voxel is translated in a series of parallel straight lines covering the whole sample and the operation is repeated at different rotation angles, thus generating one diffraction pattern per translation and rotation step. The method has been tested by imaging a specially designed phantom object, devised to be a demanding validator for X-ray diffraction imaging. The relative strengths and weaknesses of the method have been analysed with respect to the classic angle-dispersive technique. The reconstruction accuracy of the method is good, although an absorption correction is required for lower energy diffraction because of the large path lengths involved. The spatial resolution is only limited to the width of the scanning beam owing to the novel collection strategy. The current temporal resolution is poor, with a scan taking several hours. The method is best suited to studying large objects (e.g. for engineering and materials science applications) because it does not suffer from diffraction peak broadening effects irrespective of the sample size, in contrast to the angle-dispersive case